A simulation tool to optimize the management of modernized infrastructures in collective and on-farm irrigation systems - Zapata, N.; Bahddou, Sophia; Latorre, Borja; Playán, Enrique (Elsevier, 2023)
Irrigated areas face new, pressing challenges due to escalating energy costs for pumping, increasing cost of seeds, fertilizers and agrochemicals, volatility of agricultural commodities, pressure of environmental regulations, water scarcity and mounting cost of irrigation infrastructure investments. At the same time, from the technical standpoint, farmers can chose from a wide array of irrigation design and operation alternatives for collective and on-farm systems, with variable effects on crop yield and profitability. These factors are often subjected to quick changes, complicating decision making. Simulation models have proven useful to support decision making in irrigation infrastructure, water / energy use, crop agronomy and soil management. In this research, new capacities of the Ador-Simulation software are reported, targeting comprehensive analyses of irrigation modernization. The model implements additional on-farm irrigation methods (low-pressure solid-set, center-pivot and drip irrigation); crop intensification (double cropping in the same season); and crop response to different on-farm irrigation management options (timing and frequency). Model performance was verified using a set of theoretical case studies. Finally, the model was applied to the optimization of irrigation design and management (water and energy) in the Bardenas XI project of northeastern Spain. Water application in center-pivot and drip irrigation were simulated using a normal distribution characterized by a user-defined Distribution Uniformity. In center-pivot, the application depth was randomized in every irrigation event, reproducing the random nature of wind disturbances. In drip irrigation, the application depth followed the same random distribution in all irrigation events, reproducing the deterministic effect of manufacturing and hydraulic variability. According to the literature, the effect of irrigation timing was treated differently for two key sprinkler irrigated crops: corn and alfalfa. Differences in water application and crop yield between on-farm methods resulted in different gross and net income. In the Bardenas XI project, irrigation performance indicators showed different patterns of inter-annual variability. Deep percolation was strongly affected by the amount of seasonal precipitation and by Distribution Uniformity. Indicators at the plot level were strongly determined by the on-farm irrigation method, the soil type, and the crop. In the conditions of Bardenas XI, the design option without pumping station was the most adequate. Natural pressure proved sufficient for a combination of low-pressure sprinkler irrigation, pivot and drip irrigation methods, distributed throughout the irrigated area. Escalating energy costs emphasize the need for careful assessment of pumping requirements at the design phase of irrigation projects.
Keywords: On-farm irrigation methods; Irrigation modernization; Collective irrigation networks; Water use efficiency; Energy use efficiency; Low-pressure sprinkler; Simulation models